Comparison of the electrophysiological properties of the pulmonary veins between paroxysmal and persistent atrial fibrillation - Hitoshi Mori; Akira Hamabe; Daisuke Kawano; Tsukasa Naganuma; Mai Tahara; Yodo Gatate; Toyokazu Kimura; Hirotsugu Tabata; Ritsushi Kato (Journal of Arrhythmia)
Abstract Background The role of the pulmonary veins (PVs) as triggers in atrial fibrillation (AF) is well‐known; however, their detailed electrophysiological properties have not been thoroughly examined. Objective This study aimed to investigate the electrophysiological properties of the PVs between paroxysmal AF (pAF) and persistent AF (perAF). Methods Prior to catheter ablation in patients with pAF (n = 51) and perAF (n = 41), a voltage map of the left atrium and PVs was created under sinus rhythm, and the area of the myocardial sleeves in the PVs and their electrophysiological characteristics, including the pacing threshold and effective refractory period (ERP), were compared between the two groups. Results Compared with perAF, the myocardial sleeves of PVs for pAF were significantly larger for all PVs. The ERP for perAF was significantly shorter than that for pAF for all PVs. The pacing threshold for perAF was significantly higher than that for pAF for the right and left superior PVs. Conclusion In patients with perAF, a decrease in the normal myocardial sleeves and a shortening of the ERP were observed for all PVs. Those changes in the electrophysiological properties of the PVs might be related to the persistence of AF.